Agreement between self-reported perinatal outcomes and administrative data in New South Wales, Australia - Gresham, Ellie (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Many epidemiological studies that focus on pregnancy rely on maternal self-report of perinatal outcomes. The aim of this study was to evaluate the agreement between self-reported perinatal outcomes (gestational hypertension with or without proteinuria, gestational diabetes, premature birth and low birth weight) in a longitudinal study and linked to administrative data (medical records). METHODS: Self-reported survey data from the Australian Longitudinal Study on Women’s Health was linked with the New South Wales Perinatal Data Collection. Agreement between the two sources was evaluated using percentage agreement and kappa statistics. Analyses were conducted at two levels by: i) the mother and ii) each individual child. RESULTS: Women reliably self-report their perinatal outcomes (≥87 % agreement). Gestational hypertension with or without proteinuria had the lowest level of agreement. Mothers’ reports of perinatal outcomes were more reliable when evaluated by child. Restricting the analysis to complete and consistent reporting further strengthened the reliability of the child-specific data, increasing the agreement from >92 to >95 % for all outcomes. CONCLUSIONS: The present study offers a high degree of confidence in the use of maternal self-reports of the perinatal outcomes gestational hypertension, gestational diabetes, preterm birth and low birth weight in epidemiological research, particularly when reported on a per child basis. Furthermore self-report offers a cost-effective and convenient method for gathering detailed maternal perinatal histories.